2007
DOI: 10.1038/nature06268
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 regulates the histone methyl-transferase SUV39H1 during heterochromatin formation

Abstract: In contrast to stably repressive, constitutive heterochromatin and stably active, euchromatin, facultative heterochromatin has the capacity to alternate between repressive and activated states of transcription. As such, it is an instructive source to understand the molecular basis for changes in chromatin structure that correlate with transcriptional status. Sirtuin 1 (SIRT1) and suppressor of variegation 3-9 homologue 1 (SUV39H1) are amongst the enzymes responsible for chromatin modulations associated with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
389
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(411 citation statements)
references
References 16 publications
17
389
2
3
Order By: Relevance
“…Besides the histone substrates and many other nuclear factors, SIRT1 also deacetylates chromatin-modifying enzymes, including PCAF, p300, TIP60 and SUV39H1 [10,[30][31][32]. In this study, we identified hMOF as another substrate of SIRT1.…”
Section: Discussionmentioning
confidence: 80%
“…Besides the histone substrates and many other nuclear factors, SIRT1 also deacetylates chromatin-modifying enzymes, including PCAF, p300, TIP60 and SUV39H1 [10,[30][31][32]. In this study, we identified hMOF as another substrate of SIRT1.…”
Section: Discussionmentioning
confidence: 80%
“…Sirt1 belongs to the family of the mammalian homologues of the Sir2 (silent information regulator-2) of the yeast Saccharomyces cerevisiae. This is a NAD + -dependent protein deacetylase, present in cell cytoplasm and nucleus, that modulates the cell cycle, senescence, apoptosis, and metabolism by distinct mechanisms that include regulation of expression of individual genes (Picard et al 2004), condensation of chromatin (Vaquero et al 2007), or deacetylation of specific transcription factors (Brunet et al 2004). Milne and Denu (2008) described protective action of Sirt1 in aged endothelium, heart, liver, and adipose tissue, while others reported pro-aging roles of sirtuins (Longo 2009), which may be due to specific time and tissue properties of Sirt1 activity.…”
mentioning
confidence: 99%
“…To further elucidate the role of Sirt7 on Sirt1, we wanted to explore whether Sirt7 also controls other Sirt1 effects on heterochromatin. Interestingly, in an overexpression system, we observed that Sirt7 co-immunoprecipitates with the histone methyltransferase Suv39h1 (Figure 1(A)), which is bound and activated by Sirt1 [20,22] suggesting formation of a tripartite Sirt7/Sirt1/Suv39h1 complex. Co-immunoprecipitation experiments in primary mouse embryonic fibroblasts (MEFs) confirmed that endogenous Sirt7 and Suv39h1 form a molecular complex (Figure 1(B)).…”
Section: Resultsmentioning
confidence: 99%
“…Since Sirt1 positively regulates Suv39h1 activity [20] and Sirt1 becomes autodeacetylated at K230 and hyperactive in Sirt7 deficient cells [19], we speculated that hyperactivation of Sirt1 plays the decisive role for increased Suv39h1 activity in Sirt7 depleted cells. To corroborate this assumption, we expressed different combination of Sirt1, Sirt7 and Suv39h1 in HEK293T cells and monitored H3K9me3 levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation